2020
DOI: 10.3390/toxics8040082
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Thyroid Hormones between Conventional and Organic Farmers in Thailand

Abstract: Many pesticides are endocrine-disrupting chemicals that can interfere with hormone levels. This study aimed to assess the longitudinal impact of exposure to pesticides on thyroid hormone levels, including Thyroid Stimulating Hormone (TSH), Free Triiodothyronine (FT3), Free Thyroxine (FT4), Triiodothyronine (T3), and Thyroxine (T4). Both conventional (i.e., pesticide using) and organic farmers were interviewed using questionnaires, and blood samples were collected at 7–9 a.m. to determine thyroid hormone levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…The effect of various pesticides on TSH and thyroid hormone levels in healthy adults was tested (phenoxybenzoic acid (3-PBA) (metabolite of pyrethroid insecticide), trichloro-2-pyridinol (TCPY) (a metabolite of chlorpyrifos), cis and trans -3-2,2-dichlorovinyl-2,2-dimethylcyclopropane carboxylic acid ( cis and trans -DCCA) (pyrethroid metabolites), 1-napththol (1N) (a metabolite of carbaryl and naphthalene), ethylene bisdithiocarbamate (EBDC) fungicides, insecticide fipronil sulfone metabolite, dithiocarbamate fungicides, lambda-cyhalothrin (pyrethroid), paraquat (herbicide), p , p ′-dichlorodiphenyltrichloroethane (DDT), p , p ′-diphenyldichloroethene (DDE), hexachlorobenzene (HCB), alpha-chlordane, endosulphan 2, methoxychlor, beta-hexachlorocyclohexane (HCH) and mancozeb (fungicide)) ( Table 2 ). Some studies have compared TSH and thyroid hormone levels between conventional farmers (who use pesticides) and organic farmers [ 410 ]. Studies have yielded inconsistent results.…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of various pesticides on TSH and thyroid hormone levels in healthy adults was tested (phenoxybenzoic acid (3-PBA) (metabolite of pyrethroid insecticide), trichloro-2-pyridinol (TCPY) (a metabolite of chlorpyrifos), cis and trans -3-2,2-dichlorovinyl-2,2-dimethylcyclopropane carboxylic acid ( cis and trans -DCCA) (pyrethroid metabolites), 1-napththol (1N) (a metabolite of carbaryl and naphthalene), ethylene bisdithiocarbamate (EBDC) fungicides, insecticide fipronil sulfone metabolite, dithiocarbamate fungicides, lambda-cyhalothrin (pyrethroid), paraquat (herbicide), p , p ′-dichlorodiphenyltrichloroethane (DDT), p , p ′-diphenyldichloroethene (DDE), hexachlorobenzene (HCB), alpha-chlordane, endosulphan 2, methoxychlor, beta-hexachlorocyclohexane (HCH) and mancozeb (fungicide)) ( Table 2 ). Some studies have compared TSH and thyroid hormone levels between conventional farmers (who use pesticides) and organic farmers [ 410 ]. Studies have yielded inconsistent results.…”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
“…Studies have yielded inconsistent results. Pesticide use increased [ 341 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 ], decreased [ 415 , 418 , 419 , 420 ] or had no effect [ 352 , 355 , 356 , 413 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 , 429 , 430 , 431 , 432 ] on TSH levels. T4 levels either increased [ 343 , 410 , 412 , 414 , 415 , 416 , 420 , 433 , 434 , 435 ], decreased [ 344 , 410 , 416 , 421 , 422 , 423 , 426 , 427 , 428 , 429 , 433 , 436 ] or did not change [ …”
Section: Environmental Factors That Influence Tsh and Thyroid Hormone Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several epidemiologic studies have established an association between OPs and alterations of thyroid hormone levels [ 8 , 9 ]. A limited number of studies have examined whether ever using OP pesticides was associated with hypothyroidism [ 9 , 10 , 11 ], or whether use in the past growing season was related to alterations in thyroid hormone levels [ 12 , 13 , 14 ]. Experimental animal studies have also shown that organophosphate (OP) disturb thyroid gland function [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown in the larger longitudinal cohort, from which the farmers in this study were recruited, that after adjusting for covariates, thyroid hormone levels of conventional pesticide using farmers were significantly higher than those of organic farmers. Several specific herbicides had a significant relationship between the amount applied and an increase in thyroid hormone levels [ 12 ], and increasing the cumulative number of spray days of pesticides significantly increases the level of thyroid stimulating hormone (TSH) and free triiodothyronine (FT3) [ 13 ]. These farmers also had significantly higher abnormal metabolic biomarkers, body mass index (BMI), waist circumference, % body fat, triglycerides, total cholesterol, and low-density lipoprotein (LDL) values) compared to the organic farmers [ 36 ], and there was a significant association between the number of days of pesticide spraying and levels of cholesterol, high-density lipoprotein (HDL), LDL, blood pressure and BMI in the longitudinal cohort [ 37 ].…”
Section: Introductionmentioning
confidence: 99%